2006
DOI: 10.1007/s10560-006-0078-1
|View full text |Cite
|
Sign up to set email alerts
|

Absent Fathers as Providers: Race/Ethnic Differences in Support for Adolescent Mothers

Abstract: Race/ethnic differences in the prevalence of and characteristics associated with low support provided by fathers of babies born to pregnant adolescents were examined among 719 adolescent mothers who were interviewed postpartum. Low support was reported by 41.9% of AfricanAmerican, 26.2% of Mexican-American, and 19.4% of Caucasian adolescent mothers. Across race/ethnic subgroups, fathers who provided limited support were characterized by chronic substance use, gang or police involvement, or partner-directed vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
(53 reference statements)
1
17
0
Order By: Relevance
“…For example, a child with a difficult temperament can put strain in the parent-child dyad and the couple dyad, which can negatively influence the child through negative parenting. Additionally, family system theory stipulates that there are crossover effects where parents' risk levels influence their own and the other parent's parenting behaviors (Wiemann, Agurcia, Rickert, Berenson, & Volk, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, a child with a difficult temperament can put strain in the parent-child dyad and the couple dyad, which can negatively influence the child through negative parenting. Additionally, family system theory stipulates that there are crossover effects where parents' risk levels influence their own and the other parent's parenting behaviors (Wiemann, Agurcia, Rickert, Berenson, & Volk, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Although several studies have reported that adolescents who decide to continue their pregnancy frequently become single parents, the investment they put into conjugality makes evident the need to include their partners in actions aimed both at preventing the occurrence of pregnancy, and promoting positive developmental paths when pregnancy occurs (Wiemann et al 2006).…”
Section: Implications For Practicementioning
confidence: 99%
“…In other words, the occurrence (and cooccurrence) of acquiring human capital, defined here as completing high school and securing stable employment, facilitates the adolescent father's ability to meet the financial and social responsibilities of parenthood. Research links both employment and high educational attainment with father presence (Jaffee et al 2001), financial and emotional support (Wiemann et al 2006) and positive parenting (Fagot et al 1998). Still, few studies have directly examined the association between the human capital and parenting roles of adolescent fathers to discover within-group variations among adolescent fathers.…”
Section: Social Capitalmentioning
confidence: 99%
“…Although often considered as an exogenous variable, most research simply controls for human capital rather than examining the unique contribution it may have on fathering. Adolescent Father Social Capital 5 Overall, the existing literature suggests that finishing high school and securing employment is positively related to the involvement of fathers of children born to adolescent mothers (e.g., Danziger and Radin 1990;Jaffee et al 2001;Rangarajan and Gleason 1998;Wiemann et al 2006). One explanation for this association may be that these accomplishments are related to greater levels of responsibility, familial and community support networks, and competency (e.g., Dearden et al 1992;Fagot et al 1998;Futris and Pasley 2000).…”
Section: Social Capitalmentioning
confidence: 99%